2005 DDA 농업협상 대응전략 - 서진교 (한국농촌경제연구원, 2005)
The reform of the global agricultural trading system currently negotiated in the context of the World Trade Organization (WTO) is expected to have significant effects on Korean agriculture through substantial reduction of both agricultural tariffs and domestic subsidies. The objective of this study is to examine various options of efficient and practical negotiation strategies to minimize negative effects on Korean agriculture. For that purpose, positions and proposals of major players, such as the US, the EU, G-20, and G-10 are analyzed. At the same time, the agricultural tariff structures of Korea, including structural characteristics of Korean agriculture are reviewed. Main results of the study can be summarized as follows. First, it is highly recommended that Korea should have recourse to the treatment of sensitive products and special products rather than to tariff reduction formula in the field of market access. The major feature of Korean agriculture is that several products, such as rice, red pepper, and livestock, take most of agricultural production. In terms of the value of production, these products accounts for almost 70 percents of total agricultural production. The bound tariffs of these products belongs to two different tiers; 20~45 percent and over 140 percent. The products whose tariff is below 45 percent (most livestock and fruits and vegetables) is expected to be included in the lowest band. However, the products whose tariff is over 140 percents (rice, red pepper, onion, korean citrus) would be in the top band, and thus would be subject to the deepest cut of their tariff, due to the adoption of tiered formula in tariff reduction. Thus, in the market access Korea should concentrate its bargaining power on the number and treatments of sensitive products, including special products which should be subject to more flexible treatments in the tariff reduction negotiation. Second, it is more efficient and feasible to make an exception of tariff capping, rather than to try to eliminate tariff capping itself in the negotiation. Since most of Members, even the EU, agreed with the establishment of tariff capping, it is highly expected to set a ceiling at a certain level of tariff. However, it is not probable that tariff capping would be applied to all products without exceptions. For example, it is generally recognized that Japan could not accept politically tariff capping without exception because the top priority of Japan is to minimize the additional level of market opening in rice, which was already tariffied in 1999. Hence, Korea needs to prepare strategical options for obtaining exceptional cases to tariff capping; exception of tariff capping to sensitive products or at least some of sensitive products. Third, it is important to restrict the number of Special Products(SP) for getting most exceptional treatments in SP. Korea needs to actively participate to G-33 and to contribute to develop common indicators, which developed countries would agree. On domestic supports, Korea would fall into the bottom band in the reduction of both Final Bound AMS and overall trade distorting supports. However, Korea needs to make an effort to lessen reduction rate of AMS for the proper operation of rice income compensating program, which is recently introduced. In the other hand, since de-minims or new Blue Box payments are expected to be one of major policy tools of Korean agriculture in the future, it is also important to maintain appropriate level of them. Finally, it is strategical and efficient option for Korea to use several issues of export competition, which Korea takes no interest in, as a kind of negotiation leverages.